Typology of morphotypes of monastic complexes on the example of monasteries in the Kaluga region - Altunin Grigoriy V. (Архитектон)
In the course of their historical development, the architectural ensembles of the monastic complexes of the Kaluga province were growing more complex, acquiring a well-developed complex structure that would regularly include new components either in symbiosis with existing ones, organically complementing them or replacing them. This process is inextricably linked with a gradual increase in the share of built-up space and, accordingly, a decrease in open space and constant reorganization of spaces. The need to identify and rationalize formation regularities in monastic architectural ensembles makes it necessary to typify the development of both the monastery as a whole and its functional zones separately. For this purpose, it is advisable to use the same type of typological structures, the role of which may be the building morphotype of a certain functional area of the monastery’s territory.